Microbiology - Wessner, David R. , 1963-; Charles, Trevor C.; Delphy, Christine (Wiley, 2013)
This new textbook text and fully-integrated WileyPLUS teaching and learning environment promotes active learning and helps students develop a meaningful connection with the material through the incorporation of primary literature, applications and examples